Protection on Social Network Data Using Sensitive and NonSensitive Labels - Balaka Ramesh Naidu, Prabhanjana Konni (International Journal of Scientific Research and Management (IJSRM), 2015)
This Paper is motivated by the recognition of the need for a finer grain and more personalized privacy in data publication of social networks. We propose a privacy protection scheme that not only prevents the disclosure of identity of users but also the disclosure of selected features in users' profiles, Labels are denoted either as sensitive or as non-sensitive. We treat node labels both as background knowledge an adversary may possess, and as sensitive information that has to be protected. To maintain the trustworthiness, We gather the authorized information as proof. In this Social Networking site We maintain privacy and also traceability whenever he/she breaks the protocol.